Synthesis, Characterization, Thermal Analysis Study and Antioxidant Activity for Some Metal Ions Cr (III), Fe (III), Mn (II) and Pd(II) Complexes with Azo Dye Derived from p-methyl-2-hydroxybenzaldehyde - Adhraa Ghazi Abdulrazzaq; Abbas Ali Salih Al-Hamdani (مجلة بغداد للعلوم)
A new Azo Dye ligand HL was 4-((3-formyl-2-hydroxyphenyl)diazenyl)-N-(5-methylisoxazol-3-yl)benzenesulfonamide,this synthesized ligand was used for complexation with different metal ions like Cr(III), Fe(III), Mn(II) and Pd(II) by using a molar ratio of ligand: metalas 1:1. Resulted compounds were characterized by NMR (1H and 13C), UV–vis spectroscopy, TGA, DSC, FT‐IR, MS, elemental analysis, magnetic moment and molar conductivity studies. The results showed that the geometrical structural were octahedral geometries for the Cr(III), Mn(II) and Fe(III) complexes, square planer for Pd(II) complex. The antioxidant activities of the prepared compounds were assessed by using 1.1‐diphenyl‐2‐picrylhydrazyl as the free radical, and the results showed that the complex azo dye were found to possess potent antioxidant activity. The structure–activity relationship of the ligand and its complexes indicates that the presence of electron‐donating moieties, such as Cr(III), Mn(II) and Fe(III), in the chemical structure increases the antioxidant activity, whereas the Pd(II) complexes diminished the antioxidant activity, indicating the superior activity of the hydroxyl radical (OH·) over the superoxide radical.